Decoding Sacred Power: A Semio-Theological Inquiry into Wifiq Khotam Sulaiman among Javanese Muslims - Azizah, Balkis Nur; Rohman, Taufiqur; Ramadhan, Mahendra Utama Cahya (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
Despite ongoing debates around the legitimacy and theological implications of wifiq Khotam Sulaiman, its symbolic use remains prevalent in various religious and cultural contexts, including among Javanese Muslims. This study aims to (1) explore the embedded meanings behind the symbols contained in wifiq Khotam Sulaiman and (2) examine the basis of public belief and trust in its spiritual efficacy. Employing a descriptive qualitative method, this research analyzes primary textual and visual data from wifiq artifacts, supported by interviews and observations within Javanese Muslim communities. The findings reveal that wifiq Khotam Sulaiman contains seven core symbols, each representing key aspects of Prophet Sulaiman’s character and divine attributes, including references to asma’ al-a‘ẓam (the Greatest Name of God). Furthermore, public belief in the wifiq is rooted in inherited spiritual traditions that regard it as a medium of divine assistance—without attributing intrinsic power to the object itself, thus maintaining theological monotheism. Theoretically, this study contributes to the field of Islamic semiotics and symbolic theology by offering a detailed interpretation of understudied esoteric symbols. Practically, it provides insights for scholars, religious leaders, and cultural practitioners to better understand how sacred symbols function in everyday spiritual life without breaching Islamic doctrinal boundaries.